2009
DOI: 10.1007/s00586-009-0940-x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-kappa B decoy suppresses nerve injury and improves mechanical allodynia and thermal hyperalgesia in a rat lumbar disc herniation model

Abstract: Nuclear factor-kappa B (NF-jB) is a gene transcriptional regulator of inflammatory cytokines. We investigated the transduction efficiency of NF-jB decoy to dorsal root ganglion (DRG), as well as the decrease in nerve injury, mechanical allodynia, and thermal hyperalgesia in a rat lumbar disc herniation model. Forty rats were used in this study. NF-jB decoy-fluorescein isothiocyanate (FITC) was injected intrathecally at the L5 level in five rats, and its transduction efficiency into DRG measured. In another 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In a rat lumbar degenerative disc model, IκB kinase β inhibition suppressed the production of calcitonin gene related peptide, a pain-related neuropeptide, suggesting potential reduction of discogenic pain [148]. Similarly, antibodies against IL-1 or TNF-α or NF-κB decoy were able to reduce pain behaviour in animal models [149,150].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…In a rat lumbar degenerative disc model, IκB kinase β inhibition suppressed the production of calcitonin gene related peptide, a pain-related neuropeptide, suggesting potential reduction of discogenic pain [148]. Similarly, antibodies against IL-1 or TNF-α or NF-κB decoy were able to reduce pain behaviour in animal models [149,150].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…This strategy reduced nerve injury, improved mechanical allodynia and thermal hyperalgesia in this animal model (Suzuki et al, 2009) and may thus be a promising new approach but one that will require more detailed investigations in the future. A recent study revealed that systemic inhibition of NF-κB activation by the inducible IKK via chronic administration of the Nemo Binding Domain peptide inhibitor, 8K-NBD, in a mouse model of progeria (Ercc1 -/∆ mice) delayed the onset of age-related IDD (Fig.…”
Section: K Wuertz Et Al Nf-b and Mapk In The Intervertebral Discsmentioning
confidence: 99%
“…We demonstrated that nerve injury produces mechanical allodynia and thermal hyperalgesia, and NF-jB decoy was transduced into nuclei of DRG neurons in vivo leading to a decrease of mechanical allodynia and thermal hyperalgesia in rats [25]. On the other hand, we demonstrated that nerve injury caused by lumbar disc herniation produces pain-related behavior, and that a specific p38 inhibitor decreased mechanical allodynia and thermal hyperalgesia in rats [12].…”
Section: Discussionmentioning
confidence: 78%